Mediation Effectiveness in Sharia Economic Dispute Settlement: Phenomenology in Bukittinggi Religious Court - Riska Fauziah Hayati; Busyro Busyro; Bustamar Bustamar (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
The main problem in this paper is how the effectiveness of mediation in sharia economic dispute resolution based on PERMA No. 1 of 2016 at the Bukittinggi Religious Court, and what are the inhibiting factors success of mediation. To answer this question, the author uses an inductive and deductive analysis framework regarding the law effectiveness theory of Lawrence M. Friedman. This paper finds that mediation in sharia economic dispute resolution at the Bukittinggi Religious Court from 2016 to 2019 has not been effective. The ineffectiveness is caused by several factors that influence it: First, in terms of legal substance, PERMA No.1 of 2016 concerning Mediation Procedures in Courts still lacks in addressing the problems of the growing community. Second, in terms of legal structure, there are no judges who have mediator certificates. Third, the legal facilities and infrastructure at the Bukittinggi Religious Court have supported mediation. Fourth, in terms of legal culture, there are still many people who are not aware of the law and do not understand mediation well, so they consider mediation to be unimportant. Tulisan ini mengkaji tentang bagaimana efektivitas mediasi dalam penyelesaian sengketa ekonomi syariah berdasarkan PERMA Nomor 1 Tahun 2016 di Pengadilan Agama Bukittinggi dan apa saja yang menjadi faktor penghambat keberhasilan mediasi. Untuk menjawab pertanyaan tersebut, penulis menggunakan kerangka analisa induktif dan deduktif dengan mengacu pada teori efektivitas hukum Lawrence M. Friedman. Tulisan ini menemukan bahwa mediasi dalam penyelesaian sengketa ekonomi syariah di Pengadilan Agama Bukittinggi dari tahun 2016 sampai 2019 belum efektif. Hal ini karena dipengaruhi oleh beberapa faktor. Pertama, dari segi substansi hukum, yaitu PERMA No. 1 Tahun 2016 tentang Prosedur Mediasi di Pengadilan masih memiliki kekurangan dalam menjawab persoalan masyarakat yang terus berkembang. Kedua, dari segi struktur hukum, belum adanya hakim yang memiliki sertifikat mediator. Ketiga, sarana dan prasarana hukum di Pengadilan Agama Bukittinggi sudah mendukung mediasi. Keempat, dari segi budaya hukum, masih banyaknya masyarakat yang tidak sadar hukum dan tidak mengerti persoalan mediasi dengan baik, sehingga menganggap mediasi tidak penting.